Conflict in the Discourse Territory of the Agreement for Peace and a New Constitution; [la Conflictividad del Acuerdo por la Paz y la Nueva Constitución en el Territorio del Discurso*] - Hernandez-Pavez, R; Farias-Farias, M (Universidad Catolica Silva Henriquez, 2023)
This paper reports the findings from an evaluative textual analysis of a corpus of cyberpress news about the so-called Agreement for Peace and the New Constitution (APNC), published in three media: El Mostrador, Emol and La Tercera. The objective is to describe the ideological stances that underpin the social world portrayed around the APNC from a qualitative approach to the interpersonal meanings anchored in the discursive-semantic stratum of the language. The findings reveal ideological (mis) alignments, where El Mostrador legitimizes the participation of the opposition in the APNC and highlights the resistance of the right. Emol supports the political institutions and the government in relation to the agreement, and La Tercera accentuates the role of the government in the Agreement and denounces the conflicts in a sector of the opposition regarding the role of Representative Gabriel Boric. These ideological stances contribute to semantically territorialize discourse within the Agreement-Conflict and Government-Opposition axes. © 2023 Universidad Catolica Silva Henriquez. All rights reserved.